The molecular biology and biochemistry of fruit ripening - Seymour, G. B. (Graham B.) (Hoboken : Wiley-Blackwell, 2013)
A comprehensive and mechanistic perspective on fruit ripening, emphasizing commonalities and differences between fruit groups and ripening processes. Fruits are an essential part of the human diet and contain important phytochemicals that provide protection against heart disease and cancers. Fruit ripening is of importance for human health and for industry-based strategies to harness natural variation, or genetic modification, for crop improvement. This book covers recent advances in the field of plant genomics and how these discoveries can be exploited to understand evolution.
7 Cell Wall Architecture and Metabolism in Ripening Fruit and the Complex Relationship with SofteningIntroduction; Building Blocks of Fruit CellWalls; Cellulose; Hemicelluloses; Pectins; Structural Proteins; The Architecture of Fruit CellWalls; Cell Wall Dynamics in Ripening Fruit; Ripening-related Disassembly of Cell Wall Polysaccharides; Mechanisms of Cell Wall Modification; Confirmation and characterization of in vivo enzyme activities; Comparative studies of cell-wall-texture associations in different fruit species.
Evaluation of coordinated and synergistic mechanisms of cell wall disassembly.
Includes bibliographical references and index.
Online resource; title from home page (viewed August 1, 2014).
Keywords: Fruit -- Ripening; Plant molecular biology; Botanical chemistry; Botanical chemistry; Fruit -- Ripening; Plant molecular biology; GARDENING -- Fruit; TECHNOLOGY & ENGINEERING -- Agriculture -- General; Botanical chemistry; Fruit -- Ripening; Plant molecular biology; Electronic books